ФОРМУВАННЯ НАВЧАЮЧИХ СУКУПНОСТЕЙ ДЛЯ ІНФОРМАЦІЙНО- ВИМІРЮВАЛЬНИХ СИСТЕМ ДІАГНОСТИКИ ЕЛЕКТРОТЕХНІЧНОГО ОБЛАДНАННЯ З УРАХУВАННЯМ РЕЗУЛЬТАТАТІВ ЙОГО ВІБРОУДАРНИХ ВИПРОБУВАНЬ - Бондарчук, О.В.; Мислович, М.В.; Соболевська, Т.Г.; Твердяков, В.В.; Трощинський, Б.О. (Інститут електродинаміки Національної академії наук України, 2020)
The basic requirements for diagnostic systems of electric power equipment are presented, taking into account the Smart Grid concept. Some results are considered regarding the occurrence of vibration diagnostic signals in individual nodes of electrical equipment using shock influences. The main components of information support for diagnostic systems of electrical equipment are proposed, taking into account the main vibrational components that occur during external shock-vibrational excitation of the studied objects. Certain components of this software are considered, including mathematical models of diagnostic signals, as well as models that describe the multi-resonance structure of vibrations of the studied units of electrical equipment. Presented and studied are the forms of representation of training sets that correspond to certain technical conditions of the nodes of electrical equipment and take into account the multi-resonance structure of the vibrations of the nodes of electrical equipment. References 11,  figures 16.